Relationship Between Social Skills and Social Support with Peers' Academic Confidence on Boarding High School Students - Agustanti, Anisa; Astuti, Kamsih (Journal International Dakwah and Communication, 2022)
This study aims to determine: 1) the relationship between social skills and academic self-confidence in students, 2) the relationship between peer social support and academic self-confidence, and 3) the relationship between social skills and peer social support and academic self-confidence in students. The population of this study was 149 students of Boarding High School who were determined by cluster random sampling technique. The measuring instrument used is the social skills scale, the peer social support scale, and the academic self-confidence scale, arranged according to the Likert Scale method. The technical analysis of the first and second hypotheses uses the product moment correlation technique, while the third hypothesis uses the multiple regression correlation techniques. This research aims to know the relationship between social skills and academic self-confidence, the relationship between peer social support and academic self-confidence, and the relationship between social skills and peer social support and academic self-confidence. The results of the first hypothesis are that there is a positive relationship between social skills and academic self-confidence, the product-moment correlation value is 0.730, the second hypothesis is that there is a positive relationship between peer social support and academic self-confidence, the product-moment correlation value is 0.324, and the third hypothesis is that there is a relationship from social skills and peer social support with academic self-confidence, the results of the multiple regression test show that the F is 50.557. The p-value is 0.000, with an R square (R2) of 54. The results of the study state that social skills and social support from friends make an effective contribution. Peers by 54%, while the remaining 46% is influenced by other factors not examined in this study.